A case report of a patient with stage IIIa hepatocellular carcinoma complicated by early gastric cancer - Song, Xiaojing; Cai, Rangji; Wang, Lili; Ding, Fanghui; Ni, Haixu (Frontiers in Oncology, 2024)
We report a case of patient with Stage IIIa Hepatocellular Carcinoma Complicated by Early Gastric Cancer. Although Stage IIIa liver cancer can be treated with surgery, the overall prognosis of surgery is not ideal. Alternatively, conversion therapy is reported with different effectiveness towards stage IIIa liver cancer. Herein, this study shared the successful conversion of a patient with stage IIIa liver cancer and with early gastric cancer at Lanzhou University First Hospital, which is hoped to engage clinicians in evaluation and discussion.